2020
DOI: 10.3390/ani10112179
|View full text |Cite
|
Sign up to set email alerts
|

Haemoparasites—Challenging and Wasting Infections in Small Ruminants: A Review

Abstract: Haemoparasites include bacteria, mycoplasma, protozoa and flagellates inhabiting the bloodstream of living hosts. These infections occur worldwide and are transmitted by vectors, especially ticks and tsetse flies. Geographical distribution varies due to movements of animals and vectors between geographical areas, and even between countries and continents. These changes may be caused by climate change, directly and indirectly, and have a huge effect on the epidemiology of these microbes. Active and ongoing surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 60 publications
(92 reference statements)
0
29
0
Order By: Relevance
“…The main biological vectors of anaplasmosis are ticks, mainly of the genera Rhipicephalus (R. bursa and R. turanicus), Dermacentor (D. silvarum, D. marginatus and D. andersoni), Ixodes and Ambliyomma [10,11,[27][28][29]. In our study, the only tick species found in all the samples taken was Rhipicephalus turanicus.…”
Section: Discussionmentioning
confidence: 50%
“…The main biological vectors of anaplasmosis are ticks, mainly of the genera Rhipicephalus (R. bursa and R. turanicus), Dermacentor (D. silvarum, D. marginatus and D. andersoni), Ixodes and Ambliyomma [10,11,[27][28][29]. In our study, the only tick species found in all the samples taken was Rhipicephalus turanicus.…”
Section: Discussionmentioning
confidence: 50%
“…In humans, A. phagocytophilum causes human granulocytic anaplasmosis (HGA) and it is the causative agent of tick-borne fever (TBF) in sheep and goats and pasture fever in cattle [6]. TBF is a challenging and wasting condition with severe economic impact and welfare challenges in the small ruminant industry [9]. High fever (>41 • C) is the most characteristic symptom of the disease in domestic ruminants, while weakness and anorexia are also commonly reported.…”
Section: Introductionmentioning
confidence: 99%
“…or Mannheimia septicaemia, is reported due to immunosuppression. Abortion, stillbirth, reduced milk yield, impaired spermatogenesis in males, low fertility in sheep and reduced weight gain in young animals are among the most commonly occurring complications [2,6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Haemoprotozoan diseases especially Babesiosis, Anaplasmosis, Trypanosomiasis and Theileriosis are major diseases causing major constraints to the health and productivity of cattle (Ochai & Kolhatkar, 2007). Even though there is a global distribution of haemoparasites, the distribution of these infections changes continuously due to the migration and transportation of vectors and animals and an increased globalization of both live animals and their products (Stuen, 2020).…”
Section: Introductionmentioning
confidence: 99%